Development of digital books to improve Al-Qur’an reading fluency in high school students - Isnawati Amir; Nurhikmah H; Abdul Hakim (Himpunan Pengembang Kurikulum Indonesia, 2025)
Technology is developing increasingly rapidly, both in terms of economics, tourism, social and even more so in the world of education. Technology can make it easier to do various things. Education in particular has made various efforts so that students can keep up with the times with developments in science, the provision of teaching materials, supportive learning media, and professional teaching staff. This research aims to identify the need for digital books, design digital books, and measure the level of validity, practicality, and effectiveness of digital books. The problem found during initial observations was that the books were used separately. Apart from that, the ability to read the Al-Qur'an in high school students is based on Islam, a memorization program with an easy method. Al-Qur’an learning has been carried out in previous schools but is still less effective for students' Al-Qur’an reading skills following the rules of good and correct recitation. This is because the time to study Tajwid material is limited. This research combines the Borg and Gall, Four-D, and ADDIE methods, which are focused on the development of digital books. The digital book developed was declared very valid by material and media experts. The level of practicality was measured from questionnaire responses by teachers and students, and from both assessments, it was stated to be very practical. Abstrak Teknologi yang semakin cepat mengalami perkembangan, baik dari segi ekonomi, pariwisata, sosial dan terlebih lagi dalam dunia pendidikan. Teknologi bisa membuat menjadi lebih mudah untuk melakukan berbagai hal. Pendidikan khususnya, telah melakukan berbagai upaya agar peserta didiknya bisa mengikuti zaman dengan perkembangan ilmu, penyediaan bahan ajar, media pembelajaran yang mendukung, serta tenaga pendidik yang profesional. Penelitian ini bertujuan untuk mengidentifikasi kebutuhan buku digital, mendesain buku digital, mengukur tingkat validitas, kepraktisan dan keefektifan buku digital. Permasalahan yang ditemukan pada saat observasi awal adalah buku yang digunakan terpisah. Selain itu, kemampuan membaca Al-Qur’an pada peserta didik sekolah menengah atas yang berbasis Islam, program hafalan dengan metode yang mudah. Pembelajaran Al-Qur’an telah dilakukan di sekolah sebelumnya tetapi masih kurang efektif terhadap keterampilan membaca Al-Qur’an peserta didik yang sesuai dengan kaidah tajwid yang baik dan benar. Hal tersebut disebabkan karena waktu untuk mendalami materi tajwid terbatas. Penelitian ini menggabungkan metode Borg and Gall, Four-D, dan ADDIE yang difokuskan kepada pengembangan buku digital. Buku digital yang dikembangkan dinyatakan sangat valid oleh ahli materi dan media. Tingkat kepraktisannya diukur dari angket respons oleh guru dan peserta didik dan dari kedua penilaian dinyatakan sangat praktis. Kata Kunci: Al-Qur’an; buku digital; tajwid